Outcomes of Vision Therapy in Treating CVI For Post-Traumatic Brain Injury: A Case Report. - Thapa, Prabriti (Optometry & Visual Performance, 2023)
Background: Traumatic brain injury (TBI) is a growing public health concern among children and adolescents, causing death or permanent disabilities. It affects the individual's life, cognition, behaviour, and psychosocial, physical, and occupational concerns. Cortical visual impairment (CVI) is rare and typically caused by hypoxia, ischemia, and head trauma. The existence of TBI in children increases the likelihood of CVI. Therefore, prompt treatment of TBI should concentrate on preventing secondary injuries linked to worse outcomes such as CVI. Case Report: We report the case of a three-year, eleven-month-old boy accompanied by his parents who presented to the clinic 92 days after a road traffic accident. The parents complained that their child did not look at them or reach for an object when it was presented. The child was hospitalized following multiple injuries and the development of convulsions. He was diagnosed after magnetic resonance imaging (MRI) with hypoxic/ischemic brain injury resulting in acquired CVI. Upon examination, it was discovered that the child could not fixate and follow a light and had a refractive error of +5.00 DS OU. Spectacles were prescribed, and a multidisciplinary management plan was customized for the child. Treatment was based on various scientific experiment reports as no specific treatment protocol existed. After four years of intensive vision therapy, special education, and occupational therapy, the child improved in visual acuity and was more independent in performing his daily activities. Conclusion: Regardless of a patient's age and recovery time, this case report highlights the significance of vision therapy as a treatment for CVI secondary to TBI, saving the child from blindness. Clinicians should consider vision therapy in the overall rehabilitation for treating patients with CVI going forward.